Business intelligence and organizational culture : case study in a higher education company in Perú - Velásquez Goicochea, Fátima Claudia (2018)
Business Intelligence (BI) is a group of technologies, processes, methods and strategies that are focused on managing data with the purpose to create knowledge. In the last decade, many companies have been interested in Business Intelligence as a tool to enhance the decision making (strategical or tactical) process. As result, companies seeks to be competitive through BI application. However, many BI projects fail because there are factors that influence on the BI deployment and have not been taken into account. The purpose of this thesis is to prove if one of these factors is the organizational culture inside a company. In addition, it will review if the organizational culture not only has influence on the BI deployment but also on the BI maturity and on its application. For answering these questions, a case study and a survey are going to be employed. The case study is about a BI deployment in a higher educational company in Perú.